A comprehensive parametric study for hygro-thermal-vibration characteristics of the rotary composite microdisk system. Issue 1 (2nd January 2023) - Yan, Li; Wang, Xin; Wu, Haonian; Liu, Ping; Hashemabadi, Davoud
Abstract: Mechanical systems especially annular microdisks have many applications in different fields such as engineering, agriculture, and medicine. Addressed in this article, as the first attempt, is frequency and displacement analysis of a size-dependent thick rotary microsystem reinforced with graphene nanoplatelets (GPL) under hygro-thermal environment via modified couple stress theory (MCST) as the higher-order elasticity theory. The Coriolis and centrifugal effects due to the rotation are considered. The computational formulation of the microsystem, nonclassical governing equations, and corresponding boundary conditions of size-dependent thick graphene nanoplatelets reinforced composite (GPLRC) annular microsystem are derived by adding the symmetric rotation gradient and higher-order stress tensors to the strain energy. The nonclassical governing equations are solved using generalized differential quadrature method (GDQM) for various boundary conditions. The results show that the impact of radius ratio on the frequency of the system is considerable than the effect of length scale factor and the mentioned issue is more clear at higher value of rotating speed. As a good suggestion for some relevant industries, for the radius ratio ( r0 /ri ) less than 5.5 we can use the displacement filed of the microdisk and for more than 5.5 should use displacement filed of microring for modeling the microstructure. The presented outputs can be used in the structural health monitoring.